MANAGEMENT OF FISHING MANAGEMENT INFORMATION USING EXTREME PROGRAMMING - Mochamad Nandi Susila; Eka Wulansari Fridayanthie; Haryanto Haryanto (Jurnal Scientia, 2023)
There are still many traditional fishing businesses in South Tangerang, especially in the Setu and Serpong sub-districts. One of them is Abah Rimun fishing as an object of research. With current operations still relying on conventional records because a company is still based on traditional methods, there are several main gaps in the management of existing income data, such as the number of fish that have been sold or those that have been hooked by visitors and the control of funds that occur every day. This makes it challenging to monitor and search for the required data. Starting from this background, this research aims to produce a data management information system that can support operations and solve existing problems. This research uses the extreme programming software development method, with stages that are adjusted to the needs of the research object. The study results obtained an implementation of a fishing data management information system that can benefit fishing managers in managing the required data regarding visitor data and fish sold.